Unfavorable Tumor Responses to Immunotherapy in the Liver: Lessons Learned from Clinical and Preclinical Studies - Li-Chun Lu; Gen-Sheng Feng; Chih-Hung Hsu (Journal of Cancer Research and Practice)
Objective: Immunotherapy with immune checkpoint inhibitors (ICIs) has become a standard of care for many malignancies. The tumor microenvironment (TME) varies across different organs and affects tumor initiation, progression, and treatment outcomes. Organ-specific differential responses to ICIs have been observed in various cancers. The underlying mechanisms warrant further investigation. Data Sources and Study Selection: We enrolled relevant clinical and preclinical studies conducted by our groups and others. Current evidence and data were reviewed and future implication was discussed. Results: In patients with advanced hepatocellular carcinoma or esophageal cancer, non-small cell lung cancer, or melanoma with liver metastases, the efficacy of ICI-based therapy was generally lower in the liver than in other organs. The mouse liver cancer study showed that myeloid-derived suppressor cells (MDSCs) might play a role in immunosuppressive TME in the liver as compared to subcutaneous tissues; targeting MDSCs enhanced anti-tumor efficacy in the liver. The metastatic colon cancer models showed that monotherapy with anti-programmed death ligand-1 (PD-L1) antibody was less effective in suppressing tumor growth in the liver than in subcutaneous tissues. Mechanistically, modulation of hepatic innate immune cells was associated with the improved response of anti-PD-L1 antibody in the liver. Conclusion: The relatively unfavorable tumor response to immunotherapy in the liver of various cancers may be attributable to the immunosuppressive hepatic TME. Future comprehensive immune profiling is required to identify key factors and mechanisms in specific organs to overcome immunosuppressive TME, particularly in the liver.